Revision of Selatium Serène & Soh, 1970 (Crustacea: Brachyura: Sesarmidae), with description of a new genus and two new species - Schubart, Christoph D.; Liu, Hung-Chang; Ng, Peter K. L. (Zootaxa, 2009)
The Indo-West Pacific sesarmid genus Selatium Serène & Soh, 1970, is revised, and two wide-ranging species are recognized, S. brockii (De Man, 1887) and S. elongatum (A. Milne-Edwards, 1869). A new genus, Lithoselatium, which superficially resembles Selatium, is described, and two new species are recognized: L. pulchrum n. sp. from Taiwan, and L. kusu n. sp. from Singapore and nearby areas. Their relationship is discussed using both morphological and molecular datasets.